(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This article presents an analysis of scientific research carried out by scientists of the world’s textile industry on the study of cotton selection varieties to improve the quality of yarn spun from cotton fiber, which is the most important raw material of the textile industry. Also, properties and characteristics of several cotton selection varieties were analyzed. The selection of cotton varieties can have a significant impact on the quality indicators of yarn. Here are some factors to consider when analyzing the effect of cotton selection on yarn quality indicators: Fiber Length and Strength: Different cotton varieties have varying fiber lengths and strengths, which can directly impact the yarn quality. Longer fibers generally produce stronger and more durable yarn, while shorter fibers may result in weaker yarn with lower tensile strength. Micronaire Value: Micronaire value is a measure of fiber fineness and maturity, which can affect the spinning performance and yarn quality. Certain cotton varieties with optimal micronaire values can produce smoother and more even yarn, while extreme values may lead to yarn imperfections.